Systematic review and meta-analysis of hepatoprotective probiotics in vivo and elucidation of Lactiplantibacillus plantarum LAB12-induced hepatoprotection against high-fat diet-induced metabolic dysfunction-associated fatty liver disease mouse model via the gut-liver axis / Faezah Sabirin - Sabirin, Faezah (2023)
Metabolic dysfunction-associated fatty liver disease (MAFLD), previously known as non-alcoholic fatty liver disease (NAFLD), is a highly prevalent disease. To date, lifestyle modifications remain as the cornerstone for MAFLD management. During advanced stage of the disease, patients are prescribed with either vitamin E (i.e., αtocopherol) or pioglitazone. Whilst the problems of lifestyle changes are associated with poor implementation and compliance, pharmacological therapies result in limited improvement of liver pathology and are often compromised by side effects. This raises the need for effective alternatives that are relatively easier to comply with and emerging functional food like probiotics appear to fit the bill given their increasingly recognised roles in delaying the progression of MAFLD. As such, this study had first systematically reviewed publications on hepatoprotection of probiotics in vivo based on the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. The literature search, which was performed through the Cochrane Library, EMBASE, PubMed/ Medline and Web of Science by using pre-defined keywords, had identified 4,841 studies, from which 53 were shortlisted based on the inclusion and exclusion criteria. All shortlisted studies for qualitative appraisal were presented with low/ unclear risk of bias. Only 24 studies were eligible for subsequent quantitative analysis using Review Manager Version 5.3.